What was the primary mode of smallpox transmission? Implications for biodefense - Milton, Donald (Frontiers in Cellular and Infection Microbiology, 2012)
The mode of infection transmission has profound implications for effective containment by public health interventions. The mode of smallpox transmission was never conclusively established. Although “respiratory droplet” transmission was generally regarded as the primary mode of transmission, the relative importance of large ballistic droplets and fine particle aerosols that remain suspended in air for more than a few seconds was never resolved. This review examines evidence from the history variolation, data on mucosal infection collected in the last decades of smallpox transmission, aerosol measurements, animal models, reports of smallpox lung among healthcare workers, and the epidemiology of smallpox regarding the potential importance of fine particle aerosol mediated transmission. I introduce briefly the term anisotropic infection to describe the behavior of Variola major in which route of infection appears to have altered the severity of disease.